2021
DOI: 10.3390/ijms22147511
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Anti-PD-L1 Treatment in Melanoma Is Associated with the Expression of the ECM Molecule EMILIN2

Abstract: The use of immune checkpoint inhibitors has revolutionized the treatment of melanoma patients, leading to remarkable improvements in the cure. However, to ensure a safe and effective treatment, there is the need to develop markers to identify the patients that would most likely respond to the therapies. The microenvironment is gaining attention in this context, since it can regulate both the immunotherapy efficacyand angiogenesis, which is known to be affected by treatment. Here, we investigated the putative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Both are elastin microfiber interface proteins that play an important role in imparting elasticity to tissue and blood vessels ( Colombatti et al, 2000 ). Several studies have shown that EMILIN2 is associated with anti-PD1 therapy in melanoma ( Fejza et al, 2021 ). In gastric cancer, EMILIN2 regulates the proliferation of cancer cells through apoptosis ( Andreuzzi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Both are elastin microfiber interface proteins that play an important role in imparting elasticity to tissue and blood vessels ( Colombatti et al, 2000 ). Several studies have shown that EMILIN2 is associated with anti-PD1 therapy in melanoma ( Fejza et al, 2021 ). In gastric cancer, EMILIN2 regulates the proliferation of cancer cells through apoptosis ( Andreuzzi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies that highlight the coupled functions of ECM and the immune system against melanoma. For instance, in a recent study, Fejza et al presented that the ECM proteins are found to be associated with the efficacy of the PD-1 treatments [ 97 ]. Interestingly, in our study, the EC proteins were upregulated, mostly in cell adhesion components, in the late progressive phase of the tumor development and linked to the longer survival rate as well as the response to immunotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 63 DEGs in monocytes, we generated a signature of 12 overexpressed genes exhibiting immunosuppressive functions and/or associated with a poor cancer prognosis: Cd44 [34], Cd83 [35], Emp1 [36], Eif4e [37], Thbs1 [38], Vegfa [39], Emilin2 [40], Tgm2 [41], Ptgs2 [42], Fn1 [43], Crem [44] , Il1rn [45] (Fig. 5F).…”
Section: By Using Upsetplot Representations To Identify Intersection ...mentioning
confidence: 99%